INVESTIGASI KANDUNGAN RADIOISOTOP DALAM SAMPEL AIR PADA SUNGAI DISEKITAR RUMAH SAKIT - Reza Achmad Furqoni (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Nowadays radioactivity utilization is spread, for example in medicine field, agriculture, even used alternative energy from radioactivity element. In medine field, there are more hospitals that used radioactivity as one of way to healing people. This way absolutelly have implication to discarded waste from the hospital itself. Therefore, this research do for knowing radiation interval count dan activity of radioisotop mass then bring it to analyze in laboratory. The result is interval activity of radioisotop mass in sample of water 4,39 xμCi/gram – 1,59 xμCi/gram. Radioisotop contamination level is in high contamination area for alpha radiation (C > 9,99x μCi/gram) and mid contamination area for beta (9,99x μCi/gram ≥ C < 99,9x μCi/gram) in southwest from hospital. Mid contamination area for alpha radiation (0,99 x μCi/gram ≥ C < 9,99x μCi/gram) and low contamination area for beta (C < 9,99 x μCi/gram) it spread out in every track of research location. Keywords: Radioisotop Material, River Water, Hospital.